Rancang Bangun Aplikasi Pembelajaran Interaktif Untuk Anak Sekolah Dasar Kelas 1 - Nelwan, Christa Kitsy; Mamahit, Dringhuzen Jekke; Sugiarso, Brave Angkasa; Yusupa, Ade (Universitas Sam Ratulangi, 2020)
Education is a conscious and planned effort to create learning environment and learning process so students actively develop their potential. Interactive learning applications is a suitable media as learning methods for children, seeing in terms of technological developments in this era which certainly did not escape the attention of children. Therefore, to increase learning preferences of children, is to follow the conditions and situations that occur at this time. This research aims to design and build learning applications that can become interactive media that are interesting and easily understood by children. The method used is the Multimedia Development Life Cycle. This research resulted in an interactive application for grade 1 elementary school children, which was interesting, added interest in learning and was easy to use.